The Four Roles of L1 in CLIL and Translanguaging: Negotiator, Mediator, Encourager, Facilitator - Li, Chenke (Universitas Lancang Kuning, 2023)
The current landscape of English language teaching are moving from the monolingual assumption to the understanding that L1 is part of one person’s whole linguistic repertoire. However, this shift is still largely occurring in research while the practice of English teaching still largely considers L1 to be an unwanted interference. The potential role of L1 in making the input comprehensible should receive further consideration. This essay will discuss how language teachers should seek to leverage students’ L1-encoded prior knowledge rather than viewing it as an impediment within the context of Content and Language Integrated Learning (CLIL) and translanguaging because they both explicitly affirm the goal of multilingual competence and involve the use of L1 in teaching practices. The difference lies in terms of the attitudes; the use of L1 is not contemplated as a priori in CLIL yet encouraged in translanguaging. This essay highlights the need for balanced and flexible L1 use in their respective contexts and pedagogies in respect to its roles: (1) L1 can negotiate meaning for L2 learning objects, (2) L1 can address the negative transfer of false cognates, (3) L1 can encourage the engagement of multilingual resources, and (4) L1 can facilitate classroom engagement.